Ants as predators of the egg parasitoid Trichogramma cacoeciae (Hymenoptera: Trichogrammatidae) applied for biological control of the olive moth, Prays oleae (Lepidoptera: Plutellidae) in Portugal - Pereira, J.A. (2008)
The detrimental effect of predators on Trichogramma cacoeciae March. releases to control the olive moth, Prays oleae Bern., in the Trás-os-Montes region (Northeast of Portugal), was evaluated during three releases against the flower generation of the pest in 2002. At 1 and 3 h and at 1, 3, 7 and 14 days after each release, 30 Trichogramma releasing cards were examined in the field and predators were collected and identified. Furthermore, at 1, 3, 7 and 14 days after each release, the percentage of egg predation on the cards was also determined. Formicidae were the most abundant group of predators at 99.1% of the total individuals collected. Ten species were identified, Camponotus aethiops, C. lateralis, C. piceus, C. truncatus, Crematogaster auberti, C. scutellaris, Lasius niger, Leptotorax angustulus, Plagiolephis pygmaea and Tapinoma nigerrimum. T. nigerrimum was the most abundant species, both in total numbers as well as in the number of occupied cards. One day after release, the percentage of predation was 24.0% in the first release, 59.4% in the second and 38.0% in the third. Three days after release, the percentage of predation varied from 60.2 to 83.4% during the three release events. Seven days after release, the percentage of predation increased to 97.8% of the total eggs on cards.